The Determinant Factors of the Intention to Participate in Crowdfunding Activities in Jakarta Area - Gunawan, Yudith; Susanto, Kartika Dewi; Raci, Simon Rudi Lalong; Gunadi, Willy (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
The purpose of this study is to determine factors of the intention to participate in crowdfunding activities in Jakarta area. The population in this study are general consumers in Jakarta. The sample in this study are 239 respondents with the characteristics of those who had participated/not in crowdfunding activities, residing or domiciled in Jakarta. Purposive sampling technique is applied for this study, conducted by online survey in January 2019. A hypothesized model is used to analyse the relationship between the variables and tested by using SEM-PLS. The results of the study shows four hypotheses are supported and two hypotheses are rejected. The results of this study show that attitude toward helping others brings significant effect on social identification with the crowdfunding community. Furthermore, motivation, role of crowdfunding platform and social identification have significant effect on the intention to participate with the crowdfunding. However, interpersonal connectivity has no significant effect on social identification with the crowdfunding community and innovativeness has no significant effect on the intention to participate with the crowdfunding